Detection of mutated Plasmodium vivax Kelch propeller domain (PvK12) in Malaysian isolates - Shairah, Dzul; Fong, Mun Yik; Amirah, A.; Ponnampalavanar, Sasheela; Cheong, Fei Wen; Lau, Yee Ling (Malaysian Society of Parasitology and Tropical Medicine, 2018)
Malaysia is located near the borders of countries where artemisinin resistant Plasmodium falciparum (mutations in the P. falciparum Kelch propeller domain [PfK13]) have been reported. Plasmodium vivax Kelch propeller domain, PvK12, the ortholog of PfK13, could assess resistance towards artemisinin in vivax malaria. Polymorphisms in PvK12 gene were determined by PCR and sequencing was done in 300 clinical isolates collected in recent years (2012–2017) from hospitals within the country. Among 48 P. vivax samples, all were Sal-1 wild type alleles except for two isolates, a synonymous and nonsynonymous mutation respectively. The nonsynonymous (V552I) isolate was collected from an immigrant. P. vivax with mutated PvK12 is speculated to be an imported case and is likely to be circulating at very low frequency in Malaysia. An in-depth drug resistance surveillance among immigrants needs to be investigated to provide information that may be crucial for drug policy changes.